2015
DOI: 10.1128/jvi.00594-15
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Prolongs Survival of Varicella-Zoster Virus-Infected Human NeuronsIn Vitro

Abstract: Infection of human neuronsin vitrowith varicella-zoster virus (VZV) at a low multiplicity of infection does not result in a cytopathic effect (CPE) within 14 days postinfection (dpi), despite production of infectious virus. We showed that by 28 dpi a CPE ultimately developed in infected neurons and that interferon gamma inhibited not only the CPE but also VZV DNA accumulation, transcription, and virus production, thereby prolonging the life of VZV-infected neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…IFN-␥, the sole member of the type II interferon family (17), produced during viral infection stimulates transcription of cellular genes that mediate antiviral responses against several herpesviruses (18)(19)(20). IFN-␥ is produced following primary VZV infection (21,22) and inhibits VZV production in human neurons (17) and human embryonic lung fibroblasts (23). VZV reactivation correlates with a decline in IFN-␥-producing immune cells (24).…”
mentioning
confidence: 99%
“…IFN-␥, the sole member of the type II interferon family (17), produced during viral infection stimulates transcription of cellular genes that mediate antiviral responses against several herpesviruses (18)(19)(20). IFN-␥ is produced following primary VZV infection (21,22) and inhibits VZV production in human neurons (17) and human embryonic lung fibroblasts (23). VZV reactivation correlates with a decline in IFN-␥-producing immune cells (24).…”
mentioning
confidence: 99%
“…IFNγ could profoundly inhibit VZV production in ARPE-19, A549, MRC-5 but had only very limited capacity to inhibit infection in MeWo cells, where IFNβ retained the capacity to significantly reduce viral yield (120). IFNγ could also promote survival of VZV infected neurons to potentially ensure the efficient establishment of latency (121). More recently, Como and colleagues demonstrated that Type I IFNs had an inhibitory effect on VZV replication and spread in VZV infected human iPSC derived neurons in vitro (122).…”
Section: Vzv Modulation Of Ifn In Immune Cellsmentioning
confidence: 99%
“…Over the last few years, the ield of VZV latency and reactivation has greatly advanced due to the derivation of human neurons to perform mechanistic studies in vitro, and the advanced molecular techniques which have led to the identi ication of VLT in vivo [196]. Studies have shown that types I and II IFNs inhibit viral replication and that IFN-γ inhibits transcription, replication, and production of neurons derived from iPSCs [196][197][198]. Hence, IFNs could be used to induce a VZV latent phenotype in human neurons or to inhibit VZV reactivation [196].…”
Section: Animal and Other Experimental Models For Vzvmentioning
confidence: 99%